Elaboración de un alimento con base en harina de banano (Musa paradisiaca) fortificada con hierro y zinc aminoquelados, calcio microencapsulado y folato (2012)
ABSTRACT: To develop a food enriched with aminochelated iron and zinc, micro encapsulated calcium and folate for human consumption. Materials an methods: Were used banana non optimal for exportation from Urabá (Antioquia Colombia), 50% mature, arabic gum, maltodextrin, citric acid and ascorbic acid, microencapsulated milk calcium, aminochelated iron and zinc, artificial flavor, food colorants and preservatives. The product was dehydrated using a spraydrying process. Five samples of blends were subject to different temperatures by spray drying, obtaining five batches of product. The lots were subjected to bromatological and microbiology analysis, optical microscopy, acceptability testing and in vitro studies for digestibility. Results: All the batches had sensory and qualitative characteristics very similar, but the best item in the acceptability test was the number four, which corresponds to the one subjected to temperatures of input and output with a variation range of 110°C, which nutritional value is within originally proposed ranges, its flavor was one of the most widely accepted by consumers, and the microcapsule had better characterization. Conclusions: It was obtained a loose flour product, easy to dilute, enriched with micronutrients and with a good carbohydrates content, mild banana flavor, and light yellow color. Additionally, we obtained a microsphere of calcium and a well accepted product for immediate consumption.